ASSESSMENT OF THE IMPACT OF BOY-GIRL RELATIONSHIPS ON ACADEMIC PERFORMANCE AMONG PUBLIC SECONDARY SCHOOL STUDENTS IN IMENTI NORTH SUB-COUNTY, MERU KENYA - Marete, Bundi; Chiamaka, Eze Joy; Gitonga, Dr. Monica; Mwenda, Mr. Eric (IJRDO- Journal of Educational Research, 2018)
Boy-girl relationships are expressions of adolescents’ deep and strong emotional desires towards the opposite gender. They have been suggested as one of the factors influencing students’ academic performance negatively. Poor academic performance has been associated with the emotional and cognitive impact of boy-girl relationships among secondary school students in Imenti North Sub-County Meru. The purpose of this study was to assess the impact of boy-girl relationships among public secondary school students of Imenti North Sub-County, Meru, Kenya. The study was guided by the emotional effect of boy-girl relationships on academic performance among secondary school students. The study anchored on the need to belong theory which unveils the motivation behind boy-girl relationships and how maintaining frequent and consistency in the relationship can result to emotional and cognitive issues among secondary school students; which in turn affect their academic performance negatively. The study adopted a descriptive survey design. The target population for this study consisted of 72 public secondary schools; 144 teachers and 1,440 Form three students in North Imenti Sub-County. The findings of the study revealed that the emotional and cognitive effect of boy-girl relationships had adverse effect on the students’ performance. Thus, guidance and counseling departments in secondary schools should take the high prevalence of students’ past and current engagement into account when designing programs. The policy makers in the health and education sector should design policy of providing students with information about skills and attitudes on interpersonal relationships. Secondary school teachers should occasionally examine and give attention to students’ level of concentrations in their respective classes. Parents, counselors, church leaders and teachers should maintain an approachable attitude for students to discuss their personal issues as it relates to boy-girl relationships. All these can aid to mitigate the negative impact of boy-girl relationships on academic performance among secondary school students.